PRP8 intein in cryptic species of Histoplasma capsulatum: Evolution and phylogeny - Theodoro, Raquel Cordeiro (2013)
The PRP8 intein is the most widespread intein among the Kingdom Fungi. This genetic element occurs within the prp8 gene, and is transcribed and translated simultaneously with the gene. After translation, the intein excises itself from the Prp8 protein by an autocatalytic splicing reaction, subsequently joining the N and C terminals of the host protein, which retains its functional conformation. Besides the splicing domain, some PRP8 inteins also have a homing endonuclease (HE) domain which, if functional, makes the intein a mobile element capable of becoming fixed in a population. This work aimed to study (1) The occurrence of this intein in Histoplasma capsulatum isolates (n=. 99) belonging to different cryptic species collected in diverse geographical locations, and (2) The functionality of the endonuclease domains of H. capsulatum PRP8 inteins and their phylogenetic relationship among the cryptic species. Our results suggest that the PRP8 intein is fixed in H. capsulatum populations and that an admixture or a probable ancestral polymorphism of the PRP8 intein sequences is responsible for the apparent paraphyletic pattern of the LAmA clade which, in the intein phylogeny, also encompasses sequences from LAmB isolates. The PRP8 intein sequences clearly separate the different cryptic species, and may serve as an additional molecular typing tool, as previously proposed for other fungi genus, such as Cryptococcus and Paracoccidioides. © 2013 Elsevier B.V.